Hierarchical Martensite: Building Hierarchical Martensite (Adv. Funct. Mater. 7/2021). (10th February 2021) - Schwabe, Stefan; Niemann, Robert; Backen, Anja; Wolf, Daniel; Damm, Christine; Walter, Tina; Seiner, Hanuš; Heczko, Oleg; Nielsch, Kornelius; Fähler, Sebastian
Abstract : A model to describe the hierarchical microstructure of martensitic materials is presented by Sebastian Fähler and co‐workers in article number 2005715 . The microstructure can be built from scratch using several levels of nested building blocks, which allows to seamlessly explain the experimentally observed features from the atomic level all the way up to the macroscopic scale.